Green Stability Indicating Organic Solvent-Free HPLC Determination of Remdesivir in Substances and Pharmaceutical Dosage Forms - Adel Ehab Ibrahim; Sami El Deeb; Emad Mahmoud Abdelhalim; Ahmed Al-Harrasi; Rania Adel Sayed (Separations, 2021)
A green liquid chromatographic method is considered in this work to minimize the environmental impact of waste solvents. One important principle is to replace or eliminate the use of hazardous organic solvents. Organic impurities in any active pharmaceutical ingredient could arise either during the process of its synthesis, or as degradation products developed throughout the shelf-life. Remdesivir (RDS) is an antiviral drug, approved by the US Food and Drug Adminstration (-FDA), to treat SARS-Cov-2 virus during its pandemic crisis. We studied the stability of remdesivir against several degradation pathways using the organic solvent-free liquid chromatographic technique. Separation was performed on RP-C18 stationary phase using mixed-micellar mobile phase composed of a mixture of 0.025 M Brij-35, 0.1 M sodium lauryl sulfate (SLS), and 0.02 M disodium hydrogen phosphate, adjusted to pH 6.0. The mobile phase flow rate was 1 mL min−1, and detection was carried out at a wavelength of 244 nm. We profiled the impurities that originated in mild to drastic degradation conditions. The method was then validated according to International Conference of Harmonization (ICH) guidelines within a linearity range of 5–100 μg mL−1 and applied successfully for the determination of the drug in its marketed dosage form. A brief comparison was established with reported chromatographic methods, including a greenness assessment on two new metrics (GAPI and AGREE). This study is the first to be reported as eco-friendly, solvent-free, and stability indicating LC methodology for RDS determination and impurity profiling.